The crystal structure of benzyl 2,2,5,5-tetramethylthiazolidine-4-carboxylate, C15H21NO2S - Shao Lingli; Cai Shuping; Li Zhiming; Feng Yutao; Chen Mengting; Xu Kaining; Liu Zhenxiang (Zeitschrift für Kristallographie - New Crystal Structures)
C15H21NO2S, monoclinic, P21/n (no. 62), a = 12.0769(6) Å, b = 6.1507(3) Å, c = 20.4335(11) Å, β = 90.710(2)°, V = 1517.71(13) Å3, Z = 4, T = 170 K, Rgt(F) = 0.0341, wR(F2) = 0.0376.